2013
DOI: 10.1007/s00520-013-1945-x
|View full text |Cite|
|
Sign up to set email alerts
|

Initial development of the Symptom Screening in Pediatrics Tool (SSPedi)

Abstract: This study identified the lack of an appropriate symptom screening tool for use by pediatric cancer patients. A preliminary version of SSPedi was developed. Subsequent work will ensure that it is understandable by children and evaluate its psychometric properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 26 publications
0
56
0
1
Order By: Relevance
“…The monitoring system based on the rule-set was tested in a randomized control trial, which showed the preliminary effectiveness of rule-set-based e-systems [63]. Nominal group technique has also recently been used to develop consensus on the needed elements of an electronic symptom assessment questionnaire for children with cancer [64]. The authors of this study were able to develop a preliminary version of a new assessment tool and attributed a part of the success to the use of nominal group technique.…”
Section: Discussionmentioning
confidence: 99%
“…The monitoring system based on the rule-set was tested in a randomized control trial, which showed the preliminary effectiveness of rule-set-based e-systems [63]. Nominal group technique has also recently been used to develop consensus on the needed elements of an electronic symptom assessment questionnaire for children with cancer [64]. The authors of this study were able to develop a preliminary version of a new assessment tool and attributed a part of the success to the use of nominal group technique.…”
Section: Discussionmentioning
confidence: 99%
“…129,130 Once/week SSPedi SSPedi is a pediatric cancer-specific symptom screening and assessment scale measuring physical and psychological symptoms (eg, feeling angry, sad or worried, tired, mouth sores, headache, constipation or diarrhea, problems thinking or remembering, body changes, or appetite loss, among others) in 15 questions. [131][132][133] with a proxy version. 134 The SSPedi is also used in a pediatric HSCT population.…”
Section: Dailymentioning
confidence: 99%
“…Active symptom screening is important to institute treatment and prophylactic approaches in a timely fashion, thus improving quality of life. We previously noted the lack of adequate symptom screening tools available for paediatric patients with cancer 6 7. Consequently, we began the process of developing a new symptom screening tool,7 leading to the development of paper-based Symptom Screening in Pediatrics Tool (SSPedi) for use in paediatric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…We previously noted the lack of adequate symptom screening tools available for paediatric patients with cancer 6 7. Consequently, we began the process of developing a new symptom screening tool,7 leading to the development of paper-based Symptom Screening in Pediatrics Tool (SSPedi) for use in paediatric cancer. SSPedi asks about the degree to which 15 symptoms bothered the child yesterday or today on a 5-point Likert scale ranging from ‘not at all bothered’ to ‘extremely bothered’.…”
Section: Introductionmentioning
confidence: 99%